Vacuum-Assisted Closure Combined with a Myocutaneous Flap in the Management of Osteomyelitis in a Dog - Jeremy L. Shomper; Julia V. Coutin; Otto I. Lanz (Case Reports in Veterinary Medicine)
Case Description. A 2.5-year-old female spayed mixed breed dog presented to the Teaching Hospital for draining tracts on the left medial aspect of the tibia. Two years prior to presentation, the patient sustained a left tibial fracture, which was repaired with an intramedullary (IM) pin and two cerclage wires. Multiple antimicrobials were utilized during this time. Clinical Findings. Radiographs were consistent with left tibial osteomyelitis. The implant was removed and the wound was debrided. Treatment and Outcome. A bone window on the medial aspect of the tibia was created in order to facilitate implant removal. The wound and associated bone window were treated with vacuum assisted closure (VAC) in preparation for reconstructive surgery. Adjunctive VAC therapy was utilized following the caudal sartorius myocutaneous flap. Complications following this surgery included distal flap necrosis and donor site dehiscence. Clinical Relevance. This presents a difficult case of canine osteomyelitis with subsequent wound care in which VAC and a myocutaneous flap were useful adjunctive treatments for osteomyelitis. This is the first report of VAC in the management of canine osteomyelitis and management with a myocutaneous flap.